Analyzing the effects of different signs to increase the availability of designated van-accessible parking spaces. Issue 2 (3rd April 2017) - Zhang, E; White, Glen W.
ABSTRACT: Often, designated van accessible parking spaces are occupied by non-ramp or lift equipped vehicles (NRLEV) with accessible parking permits. This causes inconvenience, safety concerns, and reduced availability of parking spaces for ramp or lift equipped vehicles (RLEV). The researchers conducted a single subject design study with two settings to examine a differential comparison between the standard van sign versus intervention signs (pictorial representation of a ramp-equipped van plus messages) to determine which is more effective to signal NRLEV users not to park in designated van accessible spaces. The study was composed of two phases, a multiple treatment design to compare the effects of the intervention signs during phase 1 and a reversal design to test and validate the most effective intervention effects during phase 2. The results based on observation showed that the interventions signs could moderately reduce the chances of NRLEV users parking in the designated van accessible parking space. Implications of these research findings are discussed and recommendations for changes in state and national accessible parking policies are suggested.